Longitudinal study of parent caregiving self‐efficacy and parent stress reactions with pediatric cancer treatment procedures. Issue 7 (4th October 2012) - Harper, Felicity W. K.; Peterson, Amy M.; Uphold, Heatherlun; Albrecht, Terrance L.; Taub, Jeffrey W.; Orom, Heather; Phipps, Sean; Penner, Louis A.
Abstract Background Pain/distress during pediatric cancer treatments has substantial psychosocial consequences for children and families. We examined relationships between parents' caregiving self‐efficacy, parents' affect in response to their children's cancer‐related treatment procedures, and parents' symptoms of post‐traumatic stress at follow‐up. Methods Participants were 75 pediatric cancer patients and parents. On the day of each of three procedures (i.e., port‐start, lumbar puncture, or bone marrow aspiration), parents rated their self‐efficacy for six caregiving goals. Parents also self‐reported their negative affect (i.e., state anxiety, negative mood, and distress) in response to each procedure. Three months after the last procedure, parents reported their level of post‐traumatic stress symptoms (PTSS). Results Higher parent self‐efficacy about keeping children calm before treatment and/or keeping children calm during the procedure was associated with lower state anxiety. Self‐efficacy for keeping the child calm during procedures was significantly correlated with distress in parents at the time of procedures, and self‐efficacy for keeping the child calm before procedures was significantly correlated with PTSS. All three negative affect measures significantly mediated the effects of parents' caregiving self‐efficacy for both goals on parents' PTSS 3 months later. Conclusions Parents' caregiving self‐efficacy influences their immediate and longer‐term distress reactions to their children's treatment procedures. These findings provide a more nuanced understanding of how parents' cognitions contribute to their ability to cope with their children's treatment and suggest the benefit of an intervention that targets parents' procedure‐specific caregiver self‐efficacy. Copyright © 2012 John Wiley & Sons, Ltd.